Genome profile in a extremely rare case of pulmonary sclerosing pneumocytoma presenting with diffusely-scattered nodules in the right lung. Issue 1 (2nd January 2018) - Fan, Xiangshan; Lin, Ling; Wang, Jianjun; Wang, Yu; Feng, Anning; Nie, Ling; Wu, Hongyan; Meng, Fanqing; Xu, Haodong
ABSTRACT: Background: Pulmonary sclerosing pneumocytoma (PSP) typically presents solitary and peripheral mass, while only rarely cases display unusual multiple lesions. We reported a extremely rare case of PSP with diffusely-scattered nodules in the right lung. Case presentation: Diffusely round-shaped nodular shadows in the right lung were found by CT scan in a 31-year-old Chinese woman. The patient undergone the right pneumnectomy. Grossly, numerous small nodules, up to 2.5 cm in greatest dimension were identified in the upper, middle and lower lobes of the right lung. Histologically, the tumor presented the typical features of PSP, with a variable proportion of solid, sclerotic and papillary patterns. Immunohistochemical staining further revealed that cuboidal surface epithelial cells were positive for TTF-1, EMA, AE1/3 and vimentin (partially), and round or polygonal cells expressed TTF-1, vimentin, EMA (weakly), synaptophysin (partially), progesterone receptor (partially), and estrogen receptor (scatteredly). The patient has been followed up for 83 months after surgery by annual chest CT and no new lesions are detected in her left lung and other organs. The whole-exome sequencing identified 15 somatic mutations genes (MEGF6, DNAH5, AKT1, GPRIN2, PIK3AP1, FBXO40, HERC1, VPS16, MORN1, ZNF474, CTNNB1, ZNF251, TSC1, ATM, KDR). Pathway analysis showed possible pathways like the components of CTNNB1, AKT1, and TSC1 mutations in the PI3K/AKT signalings and AKT1, KDR and ATM in VEGF signaling pathway and AKT1 activation seemed closely related with these pathways. Conclusion: According to our and previous data, PSP with diffuse or multiple lesions is very rare, and the patients are most commonly seen in women in Asian countries. The misdiagnosis rate by clinical and intraoperative frozen-section assessment is high because of the multiple nodules in the lung and its confusing histological features. Long time follow up indicates surgical resection should not be considered as the preferred strategy for treating multiple PSP in the intralobar sites. AKT1 activation may contribute to the development of PSP while the pathogenesis of diffuse or multiple PSP still needs to be further analyzed.